ROLE OF POTASSIUM HUMATE ON GROWTH AND YIELD OF SOYBEAN AND BLACK GRAM - R.B. PATIL; A.S. KADAM; S.S. WADJE (International Journal of Pharma and Bio Sciences, 2011)
Field experiments were conducted in order to study the effect of potassium humate on growth and yield of soybean (Glycine max (L.) Merrill ) cv. Mahamendal and black gram (Phaseolus mungo (L.)) cv. Local. For the study of growth and yield characters (seedling emergence, height of plants, root length, root nodules per plant, pods per plant and yield per acre) of soybean and black gram, Seeds were sown in field plot and potassium humate 5 kg per acre per dose was applied in two doses (first dose along with sowing and second 40 days after sowing) and water as control. Growth and yield characters of crop plants were noted after various periods from seed sowing. Results obtained during this investigation clearly showed that, Potassium humate treated plants showed significantly increased on growth and yield characters of soybean and black gram than control plants.